Studi pendapatan pejala rumpon di Manggar Baru Balikpapan: Study of Pejala Rumpon Income in Manggar Baru, Balikpapan - Handayani Boa (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
Rumpon is a type of fish trap. The catch depends on the application technique. The depth in applying this gear has been recognized as the main issue for the total catch. The purpose of this study were (1) to find total user of rumpon in Manggar Baru, (2) to identify the investment value of rumpon (3) to analyze income of pejala rumpon. The research was conducted using census methods from population. Profit analysis and statistic descriptive analysis were employed to calculation investment and unprofitably. The results shown (1) The uses of rumpon increased production from one trip shorter operation, it resulted profit full operational budget, (2) investment of rumpon in Manggar Baru is Rp. 11,410,000/rumpon, ship investment is between Rp. 17.5 million-Rp. 20 million, machine Rp. 4.4 million and jala Rp. 8 million, (3) The income rumpon owner of per month is about Rp. 5.2 millions per rumpon, ship owner Rp. 2.6 millions and rumpon owner Rp. 2.6 millions and the members has Rp. 2.6 millions per rumpon, it will be higher income if fisherman also fished with other fishing gear in the same time. It is predicted that the addition income will be Rp. 500,000-Rp.1.5 millions per fisherman.